2020
DOI: 10.1093/ajcp/aqaa004
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ki-67 Expression Improves Reproducibility of Dysplasia Diagnosis in Barrett’s Esophagus

Abstract: Objectives Many studies have shown poor reproducibility among pathologists for diagnosing dysplasia in Barrett’s esophagus (BE). Immunohistochemical stains (IHC) are not widely used due to overlapping expression patterns in reactive and dysplastic processes. We hypothesized that markers involved in cell-cycle (cyclin D1, Ki-67, P16), differentiation/cell-cell interaction (β-catenin, SATB2 CD44, OCT4) and senescence (γH2AX) would produce different results in reactive and dysplastic processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The present smaller study reports similar findings, with p53 highly specific (94%) and Ki-67 highly sensitive (100%) for further dysplasia. Ki-67 expression has been reported to predict the future risk of high-grade dysplasia and EAC in patients with BE [13,31,32] and none of the patients with negative Ki-67 expression at the index endoscopy had dysplasia on follow-up endoscopy. Previous studies have reported that abnormal p53 expression predicts progression to high-grade dysplasia or EAC in patients with BE [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The present smaller study reports similar findings, with p53 highly specific (94%) and Ki-67 highly sensitive (100%) for further dysplasia. Ki-67 expression has been reported to predict the future risk of high-grade dysplasia and EAC in patients with BE [13,31,32] and none of the patients with negative Ki-67 expression at the index endoscopy had dysplasia on follow-up endoscopy. Previous studies have reported that abnormal p53 expression predicts progression to high-grade dysplasia or EAC in patients with BE [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated percentage of positive cells was ranked as 0 (negative‐10%), 1 (10%–25%), 2 (26%–50%), 3 (51%–75%) and 4 (>75%) in each tissue. Five views were taken per tissue 39,40 …”
Section: Methodsmentioning
confidence: 99%
“…Five views were taken per tissue. 39,40 For IHC of ESCC tissues, tissues were subjected to immunostaining using antibodies FAM135B. These retrospective ESCC specimens from patients after platinumbased neoadjuvant therapy were obtained from the Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei, China.…”
Section: Immunohistochemistry and Staining Scorementioning
confidence: 99%
“…LGD: occasionally (+) with cytoplasmic and membranous; HGD: often (+) with cytoplasmic and membranous [118,192,193] Ki67 BE: (+) nuclear at the base of the crypt Dysplasia: (+) diffused nuclear [119] P53 BE: (−)…”
Section: Imp3mentioning
confidence: 99%